مساهمة الخدمات الإرشادية المدرسية في الحد من ظاهرة العنف المدرسي - بزاعى, سمية; بن عمارة, سعيدة (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت الدراسة الحالية إلى التعرف على مساهمة الخدمات الإرشادية المدرسية في الحد من ظاهرة العنف المدرسي لدى تلاميذ الطور المتوسط من وجهة نظرهم بولاية باتنة بلدية عين جاسر، واستخدم المنهج الوصفي، وقام الباحث ببناء استبيان يتكون من محورين محور الخدمات الإرشادية الإنمائية واشتمل على 12 بند ومحور الخدمات الإرشادية الوقائية واشتمل على 13بند، وتم التحقق من صدقه وثباته وبعدها تم تطبيقه على عينة الدراسة والتي تكونت من 79 تلميذا وتلميذة، وبعد المعالجة الإحصائية توصلت الدراسة إلى النتائج التالية: الخدمات الإرشادية المدرسية تساهم بدرجة متوسطة في الحد من ظاهرة العنف المدرسي لدى تلاميذ الطور المتوسط من وجهة نظرهم بولاية باتنة بلدية عين جاسر من خلال ما تقدمه من خدمات إرشادية إنمائية تعمل على تعزيز قيم التسامح التي يدعو لها الدين الإسلامي، في حين الخدمات الإرشادية المدرسية الوقائية المقدمة تسهم من وجهة نظر التلاميذ في الحد من العنف المدرسي من خلال المساعي الحثيثة لمستشار التوجيه لمنع ممارسة العنف فيما بينهم. Abstract: : The aim of the current study was to identify to which school counseling services con tribute to reducing the phenomenon of violence among Middle School pupils from their perspective in Ain Djasser municipality, Batna state, Using the descriptive method, the researcher designed a questionnaire. After confirming its validity and reliability, the questionnaire was used with the study sample, which consisted of seventy-nine (79) male and female pupils. After the statistical processing, the study yielded the following results. The school counseling services contribute to a moderate degree in the reduction of the phenomenon of school violence among middle school pupils according to their point of view; through its development guidance services that promotes the values of tolerance advocatedby the Islamic religion. Whereas, from the perspective of pupils, the provided preventive school counseling services contribute to reducing school violence through strenuous efforts of guidance counselor for preventing violence among them
لدى تلاميذ الطور المتوسط من وجهة نظرهم
مقال
Keywords: خدمات إرشادية؛ مستشار التوجيه والإرشاد المدرسي والمهني؛ عنف مدرسي; counseling services; School and vocational guidance counselor; School violence